Determinant of Islamic Mutual Fund Performance: A Comparative Study Between Indonesia and Malaysia - Al Arif, Mohammad Nur Rianto; Saifullah, Aulia (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
This study aims to analyze determinant performance of Islamic equity funds and compare the performance of Indonesian Islamic equity funds with Malaysian Islamic equity funds period 2017-2019. Factors that are thought to affect the performance of mutual funds are past performance and inflation. Mutual fund performance itself is measured using the Sharpe Index. This study uses secondary data and the sample is taken using purposive sampling. Methods of data analysis using Panel Data Regression. This study indicates that simultaneously the variables Past Performance and Inflation affect the performance of Islamic equity mutual funds in Indonesia and Malaysia.Furthermore, it partially shows that Past Performance harms the performance of Islamic equity funds, while inflation positively affects the performance of Islamic equity funds. In addition, this study also shows that there is a significant difference between the performance of Indonesian and Malaysian Islamic equity funds. Malaysian Islamic equity funds were superior to Indonesian Islamic equity funds in 2017-2019.